Terminology and Legislation referring to Percutaneous Facet Procedures to Treat Low Back Pain in Brazil – Current Status - Joaquim, Andrei Fernandes; Milano, Jeronimo Buzetti; Daniel, Jefferson Walter; Mudo, Marcelo Luis; Botelho, Ricardo Vieira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Incongruities in the terminology and in the Brazilian legislation about percutaneous facet procedures (PFPs) for the treatment of chronic lower back pain are frequently the subject of litigations between health professionals and supplementary healthcare providers. The Brazilian Hierarchical Classification of Medical Procedures (CBHPM, in the Portuguese acronym) describes four types of PFPs, while the Brazilian Unified Supplementary Health Terminology (TUSS, in the Portuguese acronym) describes five distinct lumbar PFPs, which correlate with the ones described on the List of Procedures and Events in Health, created by the Brazilian National Agency of Supplementary Health (ANS, in the Portuguese acronym). In the present paper, we review the terminology of the procedures, proposing the unification of the terminology and the abolition of redundancies in the tables. Finally, we developed a single terminology proposal for the PFPs based on their complexity and objectives to be used for the treatment of lower back pain.
Keywords: percutaneous procedures; denervation; facetary; facet joints; terminology; legislation